Pengaruh BAP ( 6-Benzylaminopurine ) dan Pupuk Nitrogen terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) - Ramosta Simajuntak hidayat; Rosita Sipayung; Meiriani Meiriani (Universitas Sumatera Utara, 2015)
BAP has a fuction to accelerate the formation of buds and accelerate the growth of vegetative. Nitrogen fertilizer a fuction to inrease of vegetative growth. This reasearh was conducted at experimental field of college agriculture The Sumatera Utara University in June until August 2014. The design of the experiment was randomized block design arranged in factorial with two factors. The first factor was the BAP with 4 levels of each B0 (0 ppm), B1 (20 ppm), B2 (20 ppm) and B3 (30 ppm). The second factor was the nitrogen fertilizer with 4 level of each N0 (0 g/plant). N1 (0.4 g/plant, N2 (0.8 g/plant), N3 (1.2 g/plant). The results showed the giving of BAP until 20 ppm has a significantly effect increase plant height, number of leaves, number of bulb at 1-2 MST. The nitrogen fertilizer treatment has a significantly effect towarde plant height 8 MST, totally leaf area, plant rate growth, greenish leaf and dry weight per sample. The interaction BAP and nitrogen fertilizer has not a significantly for all parameters.Key words : 6-Benzylaminopurin, nitrogen, shallot